Herd Behaviour, Fundamental, and Macroeconomic Variables – The Driving Forces of Stock Returns: A Panel-Based Pooled Mean Group Approach - Jabeen, Shaista; Rizavi, Sayyid Salman; Farhan, Muhammad (Frontiers in Psychology, 2022)
The existing research aims to seek the herding effects on stock returns at the industry level in Pakistan Stock Exchange (PSX). Moreover, the relationship between stock returns and herding has been studied by taking some macroeconomic (Exchange rate, Interest rate, Inflation rate) and fundamental (Return on equity and Earnings per share) control variables. Herding is actually imitating other’s behaviour. This phenomenon indicates a situation where the investors follow the crowed and ignores their personal information, despite knowing the correctness of their information. Herd behaviour may drive from fundamental factors leading to efficient markets. However, it may not be associated with fundamental information causing unstable prices. The stock price data of PSX listed companies from 1999-2017 have been the point of focus. The underlying herding measure was the Cross-Sectional Absolute Deviation (CSAD), proposed by Chang et al. (2000). The significant analysis technique facilitating the current research is Pooled Mean Group (PMG)/Panel ARDL approach. Findings revealed that some sectors are evident for positive effect of herding on stock returns, whereas, some others are witnessed for its negative effects on stock returns, in both long run and short run As far as control variables are concerned, they demonstrated both significant and insignificant effects on stock returns in different sectors of PSX. The study has important implications for policymakers.